B-Site-Ordered and Disordered Structures in A-Site-Ordered Quadruple Perovskites RMn3Ni2Mn2O12 with R = Nd, Sm, Gd, and Dy - Alexei A. Belik; Ran Liu; Masahiko Tanaka; Kazunari Yamaura (Molecules)
ABO3 perovskite materials with small cations at the A site, especially with ordered cation arrangements, have attracted a lot of interest because they show unusual physical properties and deviations from general perovskite tendencies. In this work, A-site-ordered quadruple perovskites, RMn3Ni2Mn2O12 with R = Nd, Sm, Gd, and Dy, were synthesized by a high-pressure, high-temperature method at about 6 GPa. Annealing at about 1500 K produced samples with additional (partial) B-site ordering of Ni2+ and Mn4+ cations, crystallizing in space group Pn–3. Annealing at about 1700 K produced samples with disordering of Ni2+ and Mn4+ cations, crystallizing in space group Im–3. However, magnetic properties were nearly identical for the Pn–3 and Im–3 modifications in comparison with ferromagnetic double perovskites R2NiMnO6, where the degree of Ni2+ and Mn4+ ordering has significant effects on magnetic properties. In RMn3Ni2Mn2O12, one magnetic transition was found at 26 K (for R = Nd), 23 K (for R = Sm), and 22 K (for R = Gd), and two transitions were found at 10 K and 36 K for R = Dy. Curie–Weiss temperatures were close to zero in all compounds, suggesting that antiferromagnetic and ferromagnetic interactions are of the same magnitude.